"Rescue" rendezvous technique during endoscopic ultrasound‐guided gallbladder drainage for acute cholecystitis. Issue 6 (20th July 2022) - Iwano, Kosuke; Hayashi, Tsuyoshi; Katanuma, Akio
Abstract : Watch a video of this article.